The Alzheimer’s Prevention Initiative Autosomal-Dominant Alzheimer’s Disease Trial: A study of crenezumab versus placebo in preclinical PSEN1 E280A mutation carriers to evaluate efficacy and safety in the treatment of autosomal-dominant Alzheimer’s disease, including a placebo-treated noncarrier cohort (2018)
ABSTRACT: Introduction: Autosomal-dominant Alzheimer's disease (ADAD) represents a crucial population for identifying prevention strategies that might modify disease course for cognitively unimpaired individuals at high imminent risk for developing symptoms due to Alzheimer's disease (AD), that is, who have "preclinical" AD. Crenezumab is an antiamyloid monoclonal antibody that binds monomeric and aggregated forms of amyloid β, with highest affinity for oligomers; it is in development for early stages of sporadic AD and for ADAD. Methods: This is a prospective, randomized, double-blind, placebo-controlled phase 2 study of the efficacy of crenezumab versus placebo in asymptomatic PSEN1 E280A mutation carriers from family kindreds with ADAD in Colombia. Participants were randomized to receive either crenezumab or placebo for 260 weeks. The study was designed to enroll a planned total of 300 participants, including 200 preclinical mutation carriers (approximately 100 treatment, 100 placebo) and an additional control group of mutation noncarriers from the same family kindreds included to mask mutation carrier status (100 placebo only). The primary outcome is change in the Alzheimer's Prevention Initiative ADAD Composite Cognitive Test Score from baseline to week 260. Secondary outcomes include time to progression to mild cognitive impairment due to AD or dementia due to AD; changes in dementia severity, memory, and overall neurocognitive functioning; and changes in amyloid-positron emission tomography, fluorodeoxyglucose-positron emission tomography, magnetic resonance imaging volumes, and cerebrospinal fluid levels of β amyloid, tau, and p-tau. Safety and tolerability are assessed. Results: Two hundred fifty-two participants were enrolled between December 2013 and February 2017. Discussion: We describe the first large-scale, potentially label-enabling clinical trial of a preclinical treatment for ADAD. Results from this trial will inform on the efficacy of crenezumab for delaying onset of, slowing decline in, or preventing cognitive impairment in individuals with preclinical ADAD and will foster an improved understanding of AD biomarkers and their relationship to clinical outcomes. Keywords: Alzheimer's Prevention Initiative; Autosomal-dominant Alzheimer's disease; Crenezumab; Preclinical Alzheimer's disease; Prevention.